The Influence of Work Stress and Organisational Culture on Production Employees Performance of PT Kayika Waskita Indonesia Jombang - Putri, Ika Oktavia; Prasetyo, Deni Widyo (Journal of International Accounting, Taxation and Information Systems, 2024)
The aim of this research is to explore how work stress and organisational culture impact the job performance of production staff at PT Kayika Waskita Indonesia in Jombang. Data gathering involves the distribution of questionnaires, conducting interviews, observations, and documentation.   This study utilizes quantitative methods with a descriptive approach to provide an overview of the research subject based on collected data or samples.   The target population consists of production employees at PT Kayika Waskita Indonesia in Jombang. Probability sampling technique is employed to select a sample of 80 employees.   Data analysis includes validity and reliability tests, classical assumption tests, multiple linear regression analysis, hypothesis testing using t tests, and determination of the coefficient of determination (R²) with the assistance of SPSS 21 software. The findings indicate that work stress negatively and significantly affects the performance of production employees at PT Kayika Waskita Indonesia in Jombang, whereas organisational culture has a positive and significant impact on their performance.